Multiple Risk Factors for Violence to Seven Occupational Groups in the Swedish Caring Sector - Viitasara, Eija; Sverke, Magnus; Menckel, Ewa (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2003)
SummaryViolence towards health-care personnel represent an increasing problem, but little is known in terms of how different occupational groups are affected. A questionnaire was sent to a stratified sample of 2,800 of 173,000 employees in the Swedish municipal health and welfare sector. Seven major groups working with the elderly or persons with developmental disabilities were considered: administrators, nursing specialists, supervisors, direct carers, nursing auxiliaries, assistant nurses, and personal assistants. The response rate was 85 percent. Fifty-one percent of respondents reported exposure to violence or threats of violence over one year. The most vulnerable groups were assistant nurses and direct carers (usually of the developmentally disabled). Individual characteristics, such as age and organizational tenure, were related to exposure. Work-related characteristics, such as type of workplace, working full-time with clients, organizational downsizing, and high workload, were also associated with risk. Greater knowledge of impacts on different professional groups and relevant prevention are required.